Extraction of rare earth elements from end-of-life LED lamps using acid leaching - Pimassoni, Yasmim Sagrillo (2023)
The supply of rare earth elements (REE) is a growing concern due to their importance in various industries and the uncertainty in the supply of these metals. Waste electrical and electronic equipment (WEEE) represents a potentially valuable secondary source for REE recovery. However, the lack of consolidated routes and the limitation of studies to some of the 17 REE have been clear challenges. A systematic review was carried out describing the conditions and procedures applied to fluorescent lamps, cathode ray tube phosphors, neodymium magnets, nickel-metal hydride batteries, circuit boards printed, LED waste, and other secondary sources to identify gaps in the scope of ETR recovery from WEEE. Hydrometallurgical processes utilizing sulfuric acid as the primary leaching agent found extensive use. Nonetheless, there are notable gaps, such as the lack of studies on the sequential recovery of metal such as coper, iron, silver, gold, and REE metals. Additionally, there is an absence of research addressing a mixture of different wastes. LED lamps are a potential secondary source of rare earth elements, but they remain relatively little studied in the literature since there are not large numbers of studies that investigate the recovery of REE, such as cerium and yttrium, from this type of residue. Thus, to develop the first stage of the hydrometallurgical process, three leaching agents were assessed for extracting rare earth elements from printed circuit boards (PCB) and electronic components of end of-life LED lamps: nitric acid, sulfuric acid, and a combination of sulfuric acid and peroxide. The influences of temperature, acid concentration, and solid-liquid ratio were evaluated using a Box-Behnken experimental design, analyzing three levels in each factor. Process optimization revealed that the higher results were using the combination of sulfuric acid and hydrogen peroxide, with the ideal parameters of concentration of 2.5 mol.L-1, temperature of 55°C, and a solid-liquid ratio of 100 g.L-1. Although none of the variables demonstrated a statistically significant influence within the range investigated when using sulfuric acid and hydrogen peroxide, in the most favorable scenario, both temperature and solid-liquid ratio had a notable impact on the extraction process. As a direction for future research, we suggest exploring new parameter ranges based on the most favorable conditions identified in this study and also complement the evaluation with purification/recovery routes. Additionally, it may be beneficial to consider implementing a multi-stage procedure, possibly incorporating a mechanical separation step or an additional leaching phase. This approach could increase the concentration of rare earth elements in the solid material while allowing for the effective removal of base metals, making the process more efficient and economically viable.